âOrganos de expresión : espacio, memoria y tejido (2017)
This project proposes a new perspective in the understanding of machine knitting as means of expression, representing the essence and spirit of the author at the time of creating his work.Thus, from the inspiration found in the machine room located in my grandmother's apartment, I decided to appropriate her knitting machine that had been in disuse for more than a decade. As I learned it's use I started to conceive it as an extension of my own body through which it was possible to link hands knowledge, techniques and tools to make possible the act of knitting. This research, suggests thinking about machine knitting as an act to rebuild a family memory that has faded over time. In this way, tissue and memory come together as a consequence of technique and development of a knitting work. A single thread that is being attached to the points made above, indicating the...